Drive for independence : a Ralph Compton western - Compton, Ralph (Compton, Ralph. Trail drive series., 2020)
In this brand-new Ralph Compton Western, the drovers of the Bar X ranch will face sandstorms, renegades, and outlaws along the historic Cimarron trail. After a child is accidentally killed in a shootout, Art Catlin decides to give up his life of bounty hunting and finds a new career as a drover, working for the Bar X ranch. The trail is 770 miles from Santa Fe to Independence, Missouri, and Art isn't fool enough to think it'll be an easy journey. As they head east, they seem to come upon countless threats, from environmental to personal. If they're to make it all the way with the herd intact, Catlin will need to use all of the skill and knowledge he's acquired over his long and violent career.